Efektifitas Psikoedukasi Pemberian Asi Terhadap Efikasi Diri Pada Ibu Menyusui di Wilayah Kerja Puskemas Tuminting dan Puskesmas Ranomuut Manado - Rina Margaretha Kundre; Hendro Joli Bidjuni; Sefti S. J. Rompas (Jurnal Ners, 2026)
Breast milk is the primary source of nutrition for infants up to six months of age. Despite an increase in exclusive breastfeeding coverage in Indonesia, the rate remains below the national target. Maternal self-efficacy plays a crucial role in breastfeeding success, and psychoeducation has the potential to strengthen mothers’ confidence in sustaining exclusive breastfeeding. This study aimed to examine the effectiveness of breastfeeding-related psychoeducation in improving self-efficacy among breastfeeding mothers. A quasi-experimental design with a non-randomized control group pre-test post-test approach was employed in two primary health centers in Manado, Indonesia, from March to October 2023. The intervention group received psychoeducation through booklets on breastfeeding management and stress management, while the control group received no intervention. Breastfeeding self-efficacy was assessed using the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF). Data were analyzed using paired and independent t-tests.There was a statistically significant improvement in self-efficacy scores among mothers in the intervention group compared to baseline (p = 0.002). Furthermore, the post-test mean score in the intervention group was higher than in the control group, indicating the effectiveness of the intervention. Psychoeducation on breastfeeding is effective in enhancing maternal self-efficacy. This finding highlights the importance of structured psychoeducational interventions as a strategy to promote exclusive breastfeeding practices